2019
DOI: 10.1532/hsf.2415
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of In-Hospital Mortality in Isolated Total Anomalous Pulmonary Venous Connection

Abstract: Background: We assessed risk factors for early mortality in isolated total anomalous pulmonary venous connection over a modern era excluding emergent cases to eliminate the influence of associated factors on surgical outcome.  Methods: 70 patients with isolated total anomalous pulmonary venous connection who were repaired electively between January 2013 and February 2018 were included. Results: In-hospital mortality was encountered in 4 patients (5.7%). Upon univariate analysis, low age (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Moreover, in some patients, the hemodynamic status was still unstable after all of the measures mentioned above had been implemented, and an emergency operation became the only choice when the palliative techniques were abandoned, considering the aforementioned defects. Regarding the emergency operations themselves, the early mortality is similar to the result of other reports 1,3,24 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, in some patients, the hemodynamic status was still unstable after all of the measures mentioned above had been implemented, and an emergency operation became the only choice when the palliative techniques were abandoned, considering the aforementioned defects. Regarding the emergency operations themselves, the early mortality is similar to the result of other reports 1,3,24 .…”
Section: Discussionsupporting
confidence: 86%
“…Longer postoperative mechanical ventilation results in a higher risk of ventilatorassociated pneumonia and prolongs the length of stay. Additionally, studies have shown that prolonged postoperative mechanical ventilation is the most signi cant predictor of early mortality 24 . Long postoperative mechanical ventilation is usually attributed to the presence of chest infection or a worsened condition of heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low incidence of postoperative low cardiac output syndrome in our cohort (4.90%) was consistent with the recent studies. 5 , 13 4 cases with low cardiac output syndrome may be involved in cardiomyoprotection during surgery or an excessive systemic inflammatory response in the first hours after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In resource-scarce conditions in clinical practice from Vietnam, the above characteristics in 2 dead cases drawn from the present cohort can enable to more solidly contribute to numerous previous evidence regarding the increased risk factors for early mortality. 5 , 13 , 16–18 …”
Section: Discussionmentioning
confidence: 99%